آیت" سیروا فی الارض" کا تفسیری مطالعہ : پاکستانی سیاحت کے تناظر میں: Exegetical Study of the Quranic Verse “Sīrū fī al-arḍ” in the Context of Pakistani Tourism (Al-Aasar, 2025)
The Quranic verse "Sīrū fī al-arḍ" (Travel through the earth) is not merely a directive to physically move across the land; it carries profound philosophical, spiritual, and moral implications. It encourages individuals to observe the world around them, reflect upon the signs of Allah, and acknowledge His greatness, wisdom, and blessings. This divine command promotes a sense of exploration that is rooted in gratitude, learning, and awareness of one’s surroundings. In the context of Pakistan, a country richly endowed with diverse landscapes—towering mountains, serene lakes, expansive deserts, and lush valleys—this verse provides a strong foundation for promoting tourism. By aligning tourism with the Quranic principle of traveling the earth for reflection and understanding, Pakistan can elevate its tourism sector both spiritually and economically. However, despite its vast potential, the tourism industry in Pakistan faces significant challenges such as inadequate infrastructure, limited access to tourist facilities, and security concerns. These factors hinder the country from fully utilizing its natural and cultural wealth. Addressing these issues requires a well-structured and inclusive tourism policy that focuses on enhancing safety, developing road and hospitality infrastructure, and preserving historical and cultural heritage. By following the spirit of “Sīrū fī al-arḍ,” tourism in Pakistan can be transformed into a means of spiritual enrichment, economic development, and global cultural exchange. The verse not only invites people to travel but also inspires them to seek deeper meanings in nature and creation, making tourism a holistic and faith-inspired endeavor.